Molecular characterisation of FecB, FecX and FecGH mutations in Iraqi sheep breeds using RFLP-PCR technique - Al-Barzinji, Yousif M.S.; Taha, Kamaran M. (Penerbit Universiti Kebangsaan Malaysia, 2017)
The TGF-β super family, (GDF9, BMP-15 and BMPR-IB) have been shown to be essential for follicular growth and ovulation in the sheep breeds. The present study aimed to test the presence mutations of the fecundity genes association with fertility, controlling ovulation rate and litter size in four Iraqi sheep breeds (Kurdi, Hamdani, Arabi and Awassi) using specific primers designed to introduce a point mutations in PCR products of FecB1, FecB2 (BMPR-IB), FecXI, FecXB, FecXG (BMP-15) and FecGH, FecGI (GDF9) belonging to the TGF-β. A total of 140 blood samples collected from individual ewes (3-7 years) were genotyped for allelic polymorphisms using PCR-RFLP screening method. The quantity and quality of DNA was checked by Nanodrop spectrophotometer and gel electrophoresis. All genes (except the FecGH) showed wild types (non carriers ++) for all breeds and results viewed to be monomorphic with a specific restriction enzyme. Whereas, FecGH showed heterozygous carriers (H+) only in Hamdani sheep breed and this result showed that the polymorphism frequencies of FecGH gene with DedI restriction digestion significantly imbalanced in Hamdani breed compared with other breeds and the genotype frequency of HH, H+ and ++ were (0, 0.23 and 0.77) in this type of sheep. In conclusion, results suggest new possibilities for developing a breeding system for regulating fertility in Hamdani sheep breed.